The Brussels I bis Regulation and Jurisdiction over Patent Invalidity Exceptions. The Aftermath of the BSH Hausgeräte Judgment - Signorin, Stefano (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
This contribution aims to examine the recent BSH Hausgeräte judgment, in which theCourt of Justice addressed the issue of jurisdiction in cases where, within the context of an infringementaction, the defendant incidentally raises the allegedly invalidity of the patent. First and foremost, thecase is of particular significance as it allows the Court to clarify the scope of its earlier case law which,until now, had generated considerable debate and uncertainty among legal scholars and practitioners.Secondly, the Court reflects on the relationship between the Brussels regime and third States, to the extentthat the dispute at hand reveals a strong connecting factor located outside the territorial frameworkof the European Union.
Keywords: Cross-border patent litigation; Brussels regime; Infringement action; Invalidity defense; Reflexive effect